Antibody-based targeting of TNF-ligands for cancer therapy. Issue 2 (January 2015) - Bremer, Edwin
Abstract: The tumor necrosis factor (TNF) ligand and cognate TNF receptor superfamily constitute an important immunoregulatory axis pivotal for the correct execution of immune responses. TNF ligand and receptor family members among others are involved in induction of cell death in malignant cells as well as in providing co-stimulatory signals that help mount effective anti-cancer immune responses. This diverse and important regulatory role in immunity has sparked great interest in the development of TNFL/TNFR-targeted cancer immunotherapeutics. Here, I will discuss our cancer immunotherapeutic drug discovery and development program using selected examples of the TNF-ligand superfamily.